Research Updates of Plasmid-Mediated Aminoglycoside Resistance 16S rRNA Methyltransferase - Weiwei Yang; Fupin Hu (MDPI AG, 2022)
With the wide spread of multidrug-resistant bacteria, a variety of aminoglycosides have been used in clinical practice as one of the effective options for antimicrobial combinations. However, in recent years, the emergence of high-level resistance against pan-aminoglycosides has worsened the status of antimicrobial resistance, so the production of 16S rRNA methyltransferase (16S-RMTase) should not be ignored as one of the most important resistance mechanisms. What is more, on account of transferable plasmids, the horizontal transfer of resistance genes between pathogens becomes easier and more widespread, which brings challenges to the treatment of infectious diseases and infection control of drug-resistant bacteria. In this review, we will make a presentation on the prevalence and genetic environment of 16S-RMTase encoding genes that lead to high-level resistance to aminoglycosides.